Methods and techniques of teaching - Kochhar, S. K. (New Delhi : Sterling, 1985)
Contents: the genesis of modern education significant trends in modern education The teaching-learning process motivation and learning learning experiences curriculum teaching devices fixing devices audiovisual aids teaching lessons programmed instruction micro teaching simulation team teaching the kindergarten method the Montessori method the project method the Dalton plan the Gary system The heuristic method activity and playway methods basic education some classroom methods of teaching.
Keywords: Teaching